Clinical characteristics and survival outcomes of extrapulmonary neuroendocrine carcinomas: a retrospective study - Xu, Junhao; Li, Yuanyuan; Xu, Benjie; Lian, Jie; Lu, Haibo (Frontiers in Endocrinology, 2025)
BackgroundExtrapulmonary neuroendocrine carcinomas (EPNECs) are rare, heterogeneous, and aggressive malignancies with limited evidence to guide management. This study aimed to investigate the clinical characteristics, prognostic factors, and treatment outcomes of EPNEC patients.MethodsWe retrospectively analyzed 343 EPNEC patients treated at Harbin Medical University Cancer Hospital from May 2011 to December 2023. Data on demographics, primary tumor sites, tumor markers (CEA and NSE), treatments, and survival were collected. Kaplan–Meier and Cox proportional hazards models were used to evaluate prognostic factors, and subgroup analyses were performed for treatment modalities.ResultsThe median overall survival (OS) for the cohort was 23.7 months. Prognosis varied significantly by primary site, with genitourinary tumors showing the most favorable outcomes and hepatopancreatobiliary tumors the poorest. Independent predictors of worse survival included advanced stage (HR = 1.94, p < 0.001), lymph node metastasis (HR = 1.48, p = 0.02), elevated CEA (HR = 1.49, p = 0.04), and elevated NSE (HR = 1.48, p = 0.03). Patients with both CEA and NSE levels elevated had the shortest OS (p < 0.0001). Treatment effects were stage-specific: surgery improved survival only in stage I/II patients (HR = 0.26, p = 0.01), whereas chemotherapy (HR = 0.67, p = 0.02) and radiotherapy (HR = 0.45, p < 0.001) provided significant benefits in stage III/IV patients. Radiotherapy showed consistent benefit across most subgroups, including those with elevated biomarkers.ConclusionEPNEC prognosis is influenced by tumor site, stage, lymph node involvement, and biomarker levels. Surgery is optimal for early-stage disease (I/II), while chemotherapy and radiotherapy provide survival benefits in advanced-stage (III/IV) patients. Combined CEA and NSE elevation indicates a particularly poor prognosis. These findings highlight the importance of individualized, stage- and biomarker-driven therapeutic strategies for EPNECs.